Foucault Revisited – Foucault Extended (KULT_online, 2009)
The Italian philosopher Giorgio Agamben presents the distillation of his recent research in a text originally entitled Che cos’è un dispositivo? (What is a dispositive?), first published in 2006 in Italian. Using a philological methodology, Agamben exemplifies how religious épistémes influence an individual’s life and concludes with a critique of the present-day: No political party has the capacity to resist the process of “desubjectification” which is currently shaping capitalistic Western society. The ever-increasing and controlling power of “dispositives” has attained a level that makes critical opposition to it virtually impossible. Agamben gives an excellent, comprehensible description of the history and origins of the term ‘dispositive’ that follows Foucault and highlights its relevance for his own critical philosophy.